Handbook of research on seismic assessment and rehabilitation of historic structures - Asteris, Panagiotis G., 1964-; Plevris, Vagelis, 1976- (Advances in civil and industrial engineering (ACIE) book series., 2015)
"This book evaluates developing contributions in the field of earthquake engineering with regards to the analysis and treatment of structural damage inflicted by seismic activity"--